Bovine tuberculosis due to Mycobacterium bovis and other mycobacteria among water buffalo (Bubalus bubalis) from the Brazilian Amazon - Silvia Cristina da Silva Pedroso; Karla Valéria Batista Lima; Ismari Perini Furlaneto; Yan Corrêa Rodrigues; Darlene Kássia Saraiva Queiroz Pantoja; Alex Junior Souza de Souza; Washington Luiz Assunção Pereira (Journal of Infection in Developing Countries)
Introduction: Zoonotic tuberculosis is a disease of public health importance worldwide, especially in developing countries. The present study aimed to investigate the role played by Mycobacterium bovis and other mycobacteria as etiologic agents of bubaline tuberculosis (TB) in the Brazilian Amazon region.